A medieval scientific encyclopedia "renewed by goodly printing"; Wynkyn de Worde's English De proprietatibus rerum. - Holbrook, Sue Ellen (Early Science and Medicine, 1998)
Wynkyn de Worde published c. 1495 the first printed edition of John Trevisa's English translation of an influential work of science composed by Bartholomew the Englishman in Latin in the thirteenth century, De Proprietatibus Rerum (DPR). The design of de Worde's book, the use of Latin in the rubrics, and the visual vocabulary of the illustrations bring readers of English into the circle of learning. First, the plan of organization of Bartholomew's encyclopedic work is analyzed and both that structure and the expository style of the work are related to memorial reading and use as a textbook. Next, the widespread use of DPR in Latin and vernacular languages is reviewed, the suggestion that certain of its books seem to have been used more than others is made, and the reliance of English readers, such as Roger Thorney, who commissoned de Worde's edition, on de Worde for learned books printed in their provincial tongue is pointed out. Finally, through comparison with certain manuscript and other printed editions, the methods de Worde used to make the book readable are explained, the layout is shown to support the idea of system, and the function of the pictures as visual texts carrying scientific ideas is demonstrated. © Koninklijke Brill NV, Leiden, 1998.
Keywords: Encyclopedias; Great Britain; History, 15th Century; History, Medieval; Printing; Science; Translations; United Kingdom; article; book; dept.eng; history; printing; publication; science